Examining Factors Influencing Superior Study Programs for Improved Education Quality: Accreditation Ratings as a Moderator - Ramli, Nurleli; Abidin, Munirul; Waeduereh, Mustafakama (JURNAL AL-TANZIM, 2025)
This study investigates the role of superior accreditation ratings as a moderating variable in improving the quality of education in study programs within the Ministry of Religious Affairs of Indonesia. The research addresses how accreditation ratings influence program performance and enhance educational quality. Using a quantitative correlational approach, data were collected through a questionnaire distributed via Google Forms to 194 study programs, selected through simple random sampling. The data were analyzed using the SEM-PLS path model. The findings reveal that accreditation ratings positively affect study program performance, demonstrating a significant correlation between accreditation and program performance to enhance educational quality. Furthermore, accreditation ratings effectively moderate the relationship between quality standards and program performance, although accreditation alone did not significantly impact educational quality. These results suggest that superior accreditation ratings catalyze study programs implementing higher standards than the national minimum, leading to improved performance. This research provides important implications regarding the role of accreditation in improving the quality of education and can be a reference for policymakers and education managers.